Synthesis, characterization and thermal behaviour of solid-state compounds of folates with some bivalent transition metals ions - Dametto, P. R. [UNESP]; Ambrozini, B. [UNESP]; Caires, F. J. [UNESP]; Franzini, V. P. [UNESP]; Ionashiro, Massao [UNESP] (Springer Nature, 2013)
Solid-state M-L compounds, where M stands for bivalent Mn, Co, Ni, Cu and Zn and L is folate (C19H17N7O6), have been synthesized. Simultaneous thermogravimetry and differential scanning calorimetry (TG-DSC), X-ray powder diffractometry, infrared spectroscopy (FTIR), TG-DSC coupled to FTIR, elemental analysis and high-resolution continuum source flame atomic absorption spectrometry technique (HR-CS FAAS) were used to characterize and to study the thermal behaviour of these compounds. The results provided information concerning the composition, dehydration, thermal stability and thermal decomposition. © 2013 Akadémiai Kiadó, Budapest, Hungary.
Keywords: Bivalent transition metals; Characterization; Folate; Thermal behavior